Serial Inhibin B Measurements in Boys with Congenital Monorchism Indicate Compensatory Testicular Hypertrophy in Early Infancy - Hildorf, Simone; Clasen-Linde, Erik; Cortes, Dina; Fossum, Magdalena; Thorup, Jorgen (European Journal of Pediatric Surgery, 2021)
Aim Congenital monorchism is considered a condition in which an initially normal testis has existed but subsequently atrophied and disappeared due to a third trimester catastrophe (presumably torsion). Since inhibin B concentrations appear related to Sertoli and germ cells number, we evaluated pre- and postoperative inhibin B of boys with congenital monorchism to determine whether the well-known hypertrophy of the contralateral testis was reflected in inhibin B concentrations.Materials and Methods Twenty-seven boys consecutively diagnosed with congenital monorchism (median age 12 months) underwent follow-up with reproductive hormones 1 year postoperatively (median age 25 months). The results were compared with inhibin B of 225 boys with congenital nonsyndromic unilateral cryptorchidism, by converting values to multiple of the median (MoM) for age in normal boys.Results Ten boys (37%) had blind-ending vessels and ductus deferens (vanished testis) and the remaining (63%) had testicular remnants. At the time of diagnostic procedure, monorchid boys did not have significantly lower inhibin B (median 114, range 20–208) than unilateral cryptorchid boys (136, 47–393) (p = 0.27). During follow-up, MoM values of inhibin B increased in monorchid boys (median 0.59 to 0.98) and in unilateral cryptorchid boys (0.69 to 0.89) (both p < 0.0001). Compared with the concentration at surgery, an additional 44% monorchid boys had inhibin B MoM values higher than 1.0, whereas only additional 23% of unilateral cryptorchid boys exhibited such values (p = 0.04).Conclusion Generally, inhibin B MoM values were normalized during follow-up in boys with congenital monorchism, reflecting compensatory hypertrophy within the first 2.5 years of life. The compensatory capacity to increase was better in monorchism than in unilateral cryptorchidism.
Keywords: monorchism; vanished testis; testicular regression syndrome; inhibin B; compensatory testicular hypertrophy